(untitled) (Journal of Comparative & International Higher Education, 2022)
The recruitment and retention of post-secondary international students as ‘skilled’ immigrants has become a distinct form of immigration, shifting the role of higher education in society. This paper proposes the term edugration – an amalgamation of ‘education’ and ‘migration’ – to describe this system. It also argues that edugration presents an ethically ‘wicked problem’ (Rittel & Webber, 1973), requiring not only increased attention from higher/international education scholars, but also a shift in our analytic approach.